Legal Responsibility for the Circulation of Counterfeit Money in Fiqhi Jinayah Perspective - Hera Saputri, Riana; Haq, Islamul; Wahidin (Program Studi Hukum Pidana Islam IAIN Parepare, 2023)
Penelitian ini bertujuan untuk menganalisis pertimbangan hakim dalam memutus kasus tindak pidana pengedaran uang palsu di Kota Parepare dan untuk menganalisis fiqhi jinayah terhadap tindak pidana pengedaran uang palsu. Jenis penelitian ini, yaitu penelitian pustaka atau dapat dikatakan sebagai penelitian normatif yang bersifat kualitatif, serta menggunakan pendekatan kasus (case approach). Hasil penelitian ini menunjukkan bahwa pertimbangan hakim dalam memutus perkara Pengedaran Uang Palsu di kota Parepare didasarkan pada pertimbangan yuridis dan non yuridis. Pandangan Fiqih Jinayah mengenai tindak pidana pengedaran uang palsu di Kota Parepare dalam kasus ini pelaku dijatuhi berupa hukuman ta'zir dalam bentuk hukuman penjara serta denda yang ditentukan oleh hakim. This study aims to analyze the judge's considerations in deciding the criminal case of circulating counterfeit money in Parepare City and to analyze fiqhi jinayah on the crime of circulating counterfeit money. This type of research is literature research or it can be said as normative research which is qualitative in nature, and uses a case approach. The results of this study indicate that the judge's considerations in deciding the Circulation of Counterfeit Money case in the city of Parepare are based on juridical and non-juridical considerations. The view of Fiqh Jinayah regarding the crime of circulating counterfeit money in Parepare City in this case the perpetrator was sentenced to a ta'zir sentence in the form of a prison sentence and a fine determined by the judge.